Applicability of the Classroom Assessment Scoring System in Chinese Preschools Based on Psychometric Evidence. Issue 5 (3rd July 2016) - Hu, Bi Ying; Fan, Xitao; Gu, Chuanhua; Yang, Ning
ABSTRACT: Research Findings : This study examined the applicability of the Classroom Assessment Scoring System (CLASS) Pre-K (Pianta, La Paro, & Hamre, 2008) and its underpinning framework of teaching through interactions in typical Chinese kindergarten classrooms. A sample of 180 kindergarten classrooms in China was selected, and the CLASS was used to rate the classroom teaching interactions. Multiple analytical approaches were applied to examine how the CLASS functioned in the Chinese cultural and social context, including score pattern comparisons with samples from the United States and some international contexts, measurement reliability analysis for different measurement error sources (e.g., interrater reliability and stability across time), and confirmatory factor analysis for several competing models. The findings from these different analyses indicated that the CLASS exhibited the same or very similar structures as in the U.S. sample, and the ratings of the CLASS showed other desirable psychometric characteristics. Practice or Policy : The evidence from the multiple analytical approaches provide strong support for the applicability of the CLASS in the Chinese context. The findings also reveal a critical need for Chinese teachers to improve the quality of instructional support in order to promote children's optimal development. Limitations are noted, and future research directions are discussed.